Web-Based Smart Attendance System with QR Code, Geolocation, and WhatsApp Integration - M.H. Faais Al Furqoon; Handaru Jati (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2026)
Manual attendance recording in vocational high schools is still slow, vulnerable to proxy attendance, and provides parents with no timely information. This study developed a web-based student attendance system integrating QR Code scanning, geolocation validation, and automatic WhatsApp notification, and evaluated its user experience at SMK Negeri 1 Seyegan, Yogyakarta. The Research and Development approach was applied through the five stages of the Waterfall model. The system was built on the Laravel framework with a Model-View-Controller architecture and a MySQL database, while notifications were delivered through a third-party WhatsApp application programming interface. Functional verification used black box testing with eleven test cases, and user experience was measured with the standard User Experience Questionnaire of 26 items on six scales, completed by 35 respondents consisting of one homeroom teacher, one administrative staff member, and 33 students selected purposively. The data were processed with the UEQ Data Analysis Tool and compared with an international benchmark. All eleven test cases passed, giving a success rate of 100%. Five scales reached the Excellent category, namely Attractiveness 2.20, Perspicuity 2.26, Efficiency 2.32, Dependability 2.04, and Stimulation 1.98, while Novelty reached 1.51 in the Good category. Efficiency and transparency of attendance information were therefore attained at the highest quality level.